Peningkatan Kemampuan Operasi Hitung Siswa Melalui Bimbingan Belajar dan Lomba Cerdas Cermat Di Desa Simandraolo - Rohpinus Sarumaha; Yohanna Theresia Venty Fau (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
The COVID-19 outbreak had a major impact on the world of education, so the government decided to conduct online learning as an effort to break the chain of the spread of Covid-19. Online learning involves elements of technology and experiences obstacles when learning, including the network is not smooth, lack of knowledge, to the lack of student participation when learning online. This has an impact on student learning outcomes. Elementary schools in Simandraolo Village conduct online learning, especially mathematics, most students have difficulty in performing arithmetic operations such as addition, subtraction, multiplication and division of integers and fractions. Based on these problems, it is necessary to conduct tutoring activities for students so that students can be helped in overcoming the problems they experience and carry out Smart Contest activities so that students are more motivated in learning. This activity is divided into several stages as follows: preliminary stage, action stage, final stage. Based on the tutoring activities and the quiz competition, it can be concluded that students' difficulties can be overcome by conducting tutoring and quiz competitions. Based on this service activity, it is recommended that students be more active in learning. Doing exercises that are continuous and repeated so that the concepts of integer and fractional operations can be permanently embedded in the mind.